ANALISIS PENGARUH PDRB, NPL DAN BI Rate TERHADAP PENYALURAN KREDIT BPR DI KALBAR TAHUN 2007-2014 - B21112003, OCTAVIA RENANTA (Jurnal Pembangunan dan Pemerataan, 2016)
The bank is a financial institution trusted to collect funds from people and channel them back to the community in the form credit. Bank revenues are derived from channeling credit to the people. In channeling credit, there are several factors that affect the process such as the level of GRDP, NPL (Non Performing Loan), and BI Rate. The aim of this research is to examine and analyze the effect of GRDP, NPL, and the BI Rate on credit channeling at Bank Perkreditan Rakyat (People’s Credit Bank) in west Kalimantan. This research was conducted at people’s Credit Banks in West Kalimantan. This research was conducted at People’s Credit Banks in West Kalimantan in general from 2007 to 2014 in the quarterly period. The data were obtained from the publications of Central Agency of Statistics and the Regional Economic Analiysis of West Kalimantan published by Bank Indonesia. The research method used was multiple regression analysis. Research findings showed that credit channeling at People’s Credit Banks in West Kalimantan was affected by the level of GRDP, NPL, and BI Rate. The findings also indicated that GDP has a significant positive effect on credit channeling to with a significant level of 0.0000 < 0,05; NPL had a significant negative effect with a significant level of 0.0373 < 0.05; and BI Rate had significant negative effect with a significant level of 0.0056 < 0.05. simultaneously, all independent variables had a significant effect with a significant level of 0.0000 < 0.05. Keywords: GRDP, NPL, BI Rate, credit channeling at the People’s Credit Bank